Study expectations of 1st/2nd generation STEM postgraduate taught students. Issue 2 (1st April 2014) - Morgan, Michelle
Abstract : Purpose: – Although there is an increasing body of literature looking at the postgraduate student experience, there is a lack of research and knowledge in understanding the impact of postgraduate (taught) PGT students' learning experiences prior to their postgraduate study, and their expectations of studying at PGT level. The research undertaken in the Faculty of Science, Engineering and Computing at a post-1992 institution, which focuses on STEM disciplines (science, technology, engineering and mathematics), aims to correct this deficiency by providing valuable data and insights into this nationally and internationally largely neglected area. This paper seeks to report the notable findings of first and second-generation respondents. Design/methodology/approach: – Data were collected via a hard copy questionnaire that had been developed through previous research and with staff and PGT course representative input. It was distributed and completed by new taught postgraduate students during the orientation period in September 2012. It was entered into the Statistical Package for the Social Sciences (SPSS) and a range of tests were run on the data. Findings: – This original research highlights the similarities and differences between first and second-generation respondents' prior learning experiences and their expectations of studying at postgraduate taught level. Research limitations/implications: – The findings from the research presented was conducted over a one-year period and the findings are based on the limitations that such a time and financially limited project can offer. The university concerned is a post-1992 institution and has a high concentration towards teaching functions. What is observed at this UK HEI could be replicable in other teaching oriented organisations thus merits further research. Originality/value: – The findings from this original piece of research offer potentially important contributions to the current PGT debate looking at developing and expanding PGT provision and ensuring its sustainability.